Efficacy and Tolerability of Intravenous Ferric Carboxymaltose in Patients with Iron Deficiency at a Hospital Outpatient Clinic: A Retrospective Cohort Study of Real-World Clinical Practice. (3rd July 2017) - Robalo Nunes, António; Palricas Costa, Ana; Rocha, Sara Lemos; Garcia de Oliveira, Ana
Abstract : Ferric carboxymaltose (FCM) is an intravenous iron formulation to correct iron deficiency. Although its use has been extensively studied in clinical trials, real-world evidence regarding FCM treatment is scarce. Our aim was to evaluate the efficacy and tolerability of FCM treatment in patients with iron deficiency, with or without anemia, at a hospital outpatient clinic. Data was collected retrospectively from medical records. During this 2-year study, 459 patients were included. Mean age was 58.6 ± 17.5 years and most patients received cumulative FCM doses of 501–1000 mg (63.2%). Six weeks after administration of FCM, efficacy endpoints hemoglobin increase ≥2 g/dL, hemoglobin increase ≥3 g/dL, and transferrin saturation > 20% were attained by 41%, 20%, and 63% of patients, respectively. Patients who received higher FCM doses showed significant reduced odds of not achieving hemoglobin increase ≥2 g/dL (501–1000 mg, adjusted odds ratio [OR]: 0.34, 95% confidence interval [CI] 0.18–0.62; 1001–3000 mg, OR: 0.19, 95% CI 0.07–0.49), compared to 500 mg doses. Treatment-emergent adverse events were documented in <4% of patients. In conclusion, FCM treatment was effective and well-tolerated by outpatients with iron deficiency at a hospital clinic, and its dosage should be adjusted to improve iron deficiency management in clinical practice.